Synthesis of the Carbohydrate Moiety of Glycoproteins from the Parasite Echinococcus granulosus and Their Antigenicity against Human Sera - Hada, Noriyasu; Morita, Tokio; Ueda, Takashi; Masuda, Kazuki; Nakane, Hiromi; Ogane, Mami; Yamano, Kimiaki; Schweizer, Frank; Kiuchi, Fumiyuki (Molecules (Basel, Switzerland), 2021)
Stereocontrolled syntheses of biotin-labeled oligosaccharide portions containing the carbohydrate moiety of glycoprotein from Echinococcus granulosus have been accomplished. Trisaccharide Galβ1-3Galβ1-3GalNAcα1-R (A), tetrasaccharide Galα1-4Galβ1-3Galβ1-3GalNAcα1-R (B), and pentasaccharide Galα1-4Galβ1-3Galβ1-3Galβ1-3GalNAcα1-R (C), (R = biotinylated probe) were synthesized by stepwise condensation and/or block synthesis by the use of 5-(methoxycarbonyl)pentyl 2-azido-4,6-O-benzylidene-2-deoxy-α-d-galactopyranoside as a common glycosyl acceptor. The synthesis of the tetrasaccharide and the pentasaccharide was improved from the viewpoint of reducing the number of synthetic steps and increasing the total yield by changing from stepwise condensation to block synthesis. Moreover, hexasaccharide E, which contains the oligosaccharide sequence which occurs in E. granulosus, was synthesized from trisaccharide D. We examined the antigenicity of these five oligosaccharides by an enzyme-linked immunosorbent assay (ELISA). Although compounds of C–E did not exhibit antigenicity against cystic echinococcosis (CE) patient sera, compounds B, D, and E showed good serodiagnostic potential for alveolar echinococcosis (AE).